PENGARUH KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DIKOTA BATAM - Purba, Asina Marlina; Janrosl, Viola Syukrina E (LPPM Universitas Putera Batam, 2019)
Tax as one of the national development funding sources in advancing community prosperity, one of which is land and building tax. Purpose This study aims to determine the effect of awareness of taxpayers and tax sanctions on taxpayer compliance in paying land and building tax in Batam City. From the population of 4,142 samples obtained 365 respondents. The results of this study indicate that the awareness of taxpayers has a significant effect on taxpayer compliance in paying the earth and buildings, because the significant value is 0,000> 0.05, and tax sanctions also have a significant effect on taxpayer compliance in paying land and building taxes with significant value amounting to 0,000> 0.05. The results of the study show simultaneously the awareness of taxpayers and tax sanctions together have a significant effect on compliance with paying land and building taxes. The Adjusted R Square value is 0.405 or 40.5%. This means that the level of awareness of taxpayers and tax sanctions can explain the compliance variable of paying for land and building tax by 40.5% while the remaining 59.5% is influenced by other factors not included in this study. The data analysis technique used is multiple linear analysis techniques. Based on the results of the analysis it is known that the awareness of taxpayers and tax sanctions have a positive effect on taxpayer compliance in paying land taxes and buildings in Batam City.